Corneal inflammation and proliferative activity of cells of anterior epithelium in modeling bacterial keratitis and using amniotic membrane fixed with different techniques - E.V. Sereda; V.V. Vit; G.I. Drozhzhina; T.B. Gaidamaka (Ukrainian Society of Ophthalmologists, 2016)
Introduction. Molecular mechanisms of the effect of amniotic membrane (AM) on the inflammation and recover of the cornea have been investigated using various biological markers. Purpose. To determine the dependence between corneal inflammation and proliferative activity of anterior epithelium cells studying the expressions of Ki-67, CD-68, ММР-9 in a model simulating bacterial keratitis and when using amniotic membrane fixed with different techniques. Material and Methods. 60 chinchilla rabbits (60 eyes) were involved into the experimental study. The animals were induced moderate bacterial keratitis. In two weeks, the rabbits were performed AM transplantation; two techniques were used: an inlay technique with AM secured to the cornea with eight interrupted 10/00 nylon sutures, and an onlay technique with AM sutured to episclera using eight interrupted 8/00 silk sutures. Results. The study revealed the presence of negative correlation between a proliferative activity of anterior corneal epithelial cells and a degree of inflammatory infiltration of the corneal stroma as evidenced by studying such markers of corneal repair as Ki-67, CD 68 and MMP-9. If inflammation occurs, the proliferative activity of anterior epitehelium cells is reduced that significantly decreases epithelization rates and following lamellar cell differentiation. Conclusions. Inflammation and epithelization rate reduction occurs more often when AM is sutured to the corneal surface, i.g. in group of experimental animals, in which the inlay technique of AMT was used.